The effects of endurance training on muscle oxygen desaturation during incremental exercise tests: a systematic review and meta-analysis - Yogev, A.; Arnold, J. I.; Nelson, H.; Rosenblat, M. A.; Clarke, D. C.; Guenette, J. A.; Sporer, B. C.; Koehle, M. S. (Frontiers in Sports and Active Living, 2024)
Objective: Minimum muscle oxygen saturation (SmO2min) measured via near-infrared spectroscopy (NIRS) is a common measure during incremental exercise testing (IET). Our objective was to determine the effects of pre-to-post endurance training on SmO2min (DeltaSmO2min) during an IET, using a meta-analysis.